Autophagic degradation of focal adhesions underlies metastatic cancer dissemination. (4th March 2017) - Sharifi, Marina N.; Mowers, Erin E.; Macleod, Kay F.
ABSTRACT: Autophagy inhibition is being evaluated as a novel therapeutic strategy in multiple tumor types, but little is known about its implications for metastatic dissemination. We recently reported that autophagic degradation of paxillin through direct interaction with the autophagy protein LC3B is required for focal adhesion disassembly, Src-stimulated tumor cell motility, and metastasis.